2014
DOI: 10.1002/chem.201400349
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Free Reduction of CO2 with Hydroboranes: Two Efficient Pathways at Play for the Reduction of CO2 to Methanol

Abstract: Guanidines and amidines prove to be highly efficient metal-free catalysts for the reduction of CO2 to methanol with hydroboranes such as 9-borabicyclo[3.3.1]nonane (9-BBN) and catecholborane (catBH). Nitrogen bases, such as 1,5,7-triazabicyclo[4.4.0]dec-5-ene (TBD), 7-methyl-1,5,7-triazabicyclo[4.4.0]dec-5-ene (Me-TBD), and 1,8-diazabicycloundec-7-ene (DBU), are active catalysts for this transformation and Me-TBD can catalyze the reduction of CO2 to methoxyborane at room temperature with TONs and TOFs of up to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 157 publications
(83 citation statements)
references
References 194 publications
(229 reference statements)
5
77
1
Order By: Relevance
“…Although the catalytic performances are modest, these results are interesting as neither the parent guanidine base TBD nor the dimeric boron analogue III, nor the N/B FLP-CO 2 adduct V (Scheme 2) show any catalytic activity with catBH and pinBH. 27 The same trends in reactivity are observed for catBH and 9-BBN when catalyst 1 is replaced with iPr 1, Ph Table 1). All together, these results suggest that the formation of a CO 2 -adduct (e.g., 2) facilitates the catalytic hydroboration of CO 2 with 9-BBN and catBH.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Although the catalytic performances are modest, these results are interesting as neither the parent guanidine base TBD nor the dimeric boron analogue III, nor the N/B FLP-CO 2 adduct V (Scheme 2) show any catalytic activity with catBH and pinBH. 27 The same trends in reactivity are observed for catBH and 9-BBN when catalyst 1 is replaced with iPr 1, Ph Table 1). All together, these results suggest that the formation of a CO 2 -adduct (e.g., 2) facilitates the catalytic hydroboration of CO 2 with 9-BBN and catBH.…”
Section: ■ Results and Discussionsupporting
confidence: 71%
“…CO 2 -adducts are often described as key-intermediates in the catalytic cycle of the CO 2 reduction processes, 25,57 and both adducts IV and V were shown to react with an electrophilic borane (9-BBN) to yield formate species. 27 In light of these data and the reaction chemistry of 1 described above, activation of CO 2 by 1 is a reasonable starting point for the hydroboration of CO 2 with 1 (Scheme 4). DFT calculations, performed at the M05-2X/ PCM = THF/6-31+G* (6-311++G** for the active hydride) level of theory confirm that the formation of a CO 2 adduct [2 + ,Cl − ] from 1 is indeed exergonic by −6.1 kcal/mol with a low activation barrier of only 10.6 kcal/mol (Scheme 4).…”
Section: ■ Results and Discussionmentioning
confidence: 98%
“…Cantat et al. reported hydroboration of CO 2 with a guanidine base . On the basis of mechanistic studies, it was proposed that guanidine bonding to the borane enables nucleophilic attack at the CO 2 .…”
Section: Methodsmentioning
confidence: 99%
“…Cantat et al [45] showed that nitrogenous bases can catalyze the reduction of CO 2 to methoxide with hydroboranes as the reductant. Specifically, guanidines and amidines such as TBD and Me-TBD are efficient catalysts for the hydroboration of CO 2 .…”
Section: Methodsmentioning
confidence: 99%